Experimental study and clustering of operating staff of search systems in the sense of stress resistance - Shakhovska, Nataliya; Kaminskyi, Roman; Khudoba, Bohdan (Frontiers in Big Data, 2023)
Introduction The main goal of this study is to develop a methodology for the organization of experimental selection of operator personnel based on the analysis of their behavior under the influence of micro-stresses. Methods A human-machine interface model has been developed, which considers the change in the functional state of the human operator. The presented concept of the difficulty of detecting the object of attention contributed to developing a particular sequence of ordinary test images with stressor images included in it and presented models of the flow of presenting test images to the recipient. Results With the help of descriptive statistics, the parameters of individual box-plot diagrams were determined, and the recipient group was clustered. Discussion Overall, the proposed approach based on the example of the conducted grouping makes it possible to ensure the objectivity and efficiency of the professional selection of applicants for operator specialties.